The Bioarchaeology of Structural Violence A Theoretical Framework for Industrial Era Inequality - Tremblay, Lori A.; Reedy, Sarah; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This volume is a resource for bioarchaeologists interested in using a structural violence framework to better understand and contextualize the lived experiences of past populations. One of the most important elements of bioarchaeological research is the study of health disparities in past populations. This book offers an analysis of such work, but with the benefit of an overarching theoretical framework. It examines the theoretical framework used by scholars in cultural and medical anthropology to explore how social, political, and/or socioeconomic structures and institutions create inequalities resulting in health disparities for the most vulnerable or marginalized segments of contemporary populations. It then takes this framework and shows how it can allow researchers in bioarchaeology to interpret such socio-cultural factors through analyzing human skeletal remains of past populations. The book discusses the framework and its applications based on two main themes: the structural violence of gender inequality and the structural violence of social and socioeconomic inequalities.
Chapter 1. Introduction (Lori A. Tremblay And Sarah Reedy) -- Part I: The Structural Violence of Gender Inequality -- Chapter 2. Female beauty, bodies, binding, and the bioarchaeology of structural violence in the industrial era through the lens of critical white feminism (Pamela K. Stone) -- Chapter 3. Embodied discrimination and (3z(Bmutilated historicity(3y(B: Archiving black women$1 (Bs bodies in the Huntington collection (Aja M. Lans) -- Chapter 4. Embodying industrialization: Inequality, structural violence, disease, and stress in working class and poor British women (Sarah Mathena-Allen and Molly K. Zuckerman). Chapter 5. Patriarchy in Industrial Era Europe: Skeletal evidence of male preference during growth (Sarah Reedy) -- Part II: The Structural Violence of Social and Socioeconomic Inequalities -- Chapter 6. The Erie County Poorhouse (1828-1926) as a Heterotopia: A bioarchaeological perspective (Jennifer L. Muller, Jennifer F. Byrnes, and David A. Ingleman) -- Chapter 7. Norway$1 (Bs Industrial Beginnings: New life challenges, recurring poverty, and the path to Tukthuset, Oslo House of Corrections (Gwyn Madden and Rose Drew) -- Chapter 8. A new division of labor? Understanding structural violence through occupational stress: An examination of entheseal patterns and osteoarthritis in the Hamann-Todd collection (Anna Paraskevi Alioto) -- Chapter 9. Products of industry: Pollution, health, and England$1 (Bs Industrial Revolution (Sara A. McGuire) -- Chapter 10. Health, well-being, and structural violence after sociopolitical revolution (Gina M. Agostini) -- Chapter 11. Structural violence in antebellum New Orleans: How the interplay of socioeconomic status and law impacted the class structure of Louisiana$1 (Bs port populations (Christine L. Halling and Ryan M. Seidemann) -- Chapter 12. Conclusion (Sarah Reedy).s
Keywords: Social history; Archaeology; Social sciences$1 (BPhilosophy.s; Social History; Archaeology; Social Theory